Phytotoxic Activity of the Natural Compound Norharmane on Crops, Weeds and Model Plants - David López-González; David Ledo; Luz Cabeiras-Freijanes; Mercedes Verdeguer; Manuel J. Reigosa; Adela M. Sánchez-Moreiras (Plants, 2020)
Norharmane is a secondary metabolite that appears in different species of land plants. In this paper, we investigated for the first time the specificity of norharmane through germination and growth tests on some crops as Zea mays L. (maize), Triticum aestivum L. (wheat), Oryza sativa L. (rice) and Lactuca sativa L. (lettuce) and weeds as Amaranthus retroflexus L. (amaranth), Echinochloa crus-galli L. (barnyard grass), Plantago lanceolata L. (ribwort), Portulaca oleracea L. (common purslane) and Avena fatua L. (wild oat), and its phytotoxic capacity on the metabolism of adult Arabidopsis thaliana L. (thale cress) by measuring chlorophyll a fluorescence, pigment content, total proteins, osmotic potential and morphological analysis. Norharmane had an inhibitory effect on the germination of A. fatua and P. lanceolata, and the growth of P. oleracea, E. crus-galli and A. retroflexus. On adult A. thaliana plants, the compound was more effective to watering, leading to water stress that compromised the growth of the plants and ultimately affected the photosynthetic apparatus. Therefore, this research shows that norharmane not only affects seedlings’ metabolism, but also damages the metabolism of adult plants and can be a potential model for a future bioherbicide given its specificity.